Rancang Bangun Aplikasi Pembayaran Biaya Operasional Pendidikan pada PG-TK Al-Zaitun Sidoarjo Berbasis Website - Miftahussalam, Moh.; Sutomo, Erwin; Wulandari, Sri Hariani Eko (Jurnal Sistem Informasi Universitas Dinamika (JSIKA), 2018)
This research is motivated by the problems faced by the administration in making payment PMB registration, re-registration and payment of tuition payment per month is still done manually so that the schools often miss evidence of payment has been recorded. Then in making a payment summary report can be spent primarily to determine a decision as anyone who has not made a payment. The solution provided is creating and designing applications operating expenses based education website,because it can minimize recording errors and report transactions that may occur if done manually. Based on the trial results indicate that these applications can be overcome and reduce the problems that occur in the process of education operating expenses. In addition, the application also allows the administration when where a student is late to pay spp system will automatically send SMS notifications to parents in the form of a guardian.Â Keywords: Payments, Operating Expenses of Education, PG-TK Al-Olive Waru Sidoarjo